Pengaruh Pendapatan Premi, Klaim, Invetasi dan Biaya Operasional Terhadap Pertumbuhan Aset Perusahaan Asuransi Jiwa Syariah Di Indonesia - Fatmawati, Novia Dwi; Devy, Happy Sista (Velocity: Journal of Sharia Finance and Banking, 2021)
This research aims to see the effect of insurance premium income, claims, investment and operating cost on the growth of Islamic life insurance companies in Indonesia. Research method ini this research, used the multiple linear regression using the SPSS 22 program. The sampling technique used is purposive sampling with the population being sharia life insurance companies in Indonesia which are listed in the OJK in 2015-2019. The results showed that insurance premium income has a positive and significant effect on asset growth, while claims and operating cost have a negative and significant effect, so it can be concluded that the greater the insurance premium higher growth of the company's assets , while the claims and operating expenses apply the opposite. Investment in its effect on asset growth shows insignificant results.